Genetics in Idiopathic Pulmonary Fibrosis Pathogenesis, Prognosis, and Treatment - Kaur, Amarpreet; Mathai, Susan K.; Schwartz, David A. (Frontiers in Medicine, 2017)
Idiopathic pulmonary fibrosis (IPF), the most common form of idiopathic interstitial pneumonia (IIP), is characterized by irreversible scarring of the lung parenchyma and progressive decline in lung function leading to eventual respiratory failure. The prognosis of IPF is poor with a median survival of three to five years after diagnosis and no curative medical therapies. Though the pathogenesis of IPF is not sufficiently knownnot well understood, there is a increasing growing body of evidence that genetic factors predispose individuals to develop IPFcontribute to disease risk. Recent studies have identified common and rare genetic variants associated with both sporadic and familial forms of pulmonary fibrosis, with at least . Current data suggests that at least one-third of the risk for developing fibrotic IIP and IPF can be explained by common genetic variants. In addition, some common variants have also been associated with distinct clinical phenotypes. The IPF-associated genetic loci discovered to date are associated with IPF are implicated in diverse biological processes, including alveolar stability, host defense, cell-cell barrier function, and cell senescence. In addition, some common variants have also been associated with distinct clinical phenotypes. Identification of gene variants associated with IPF and with IPF-associated mortalityBetter understanding of how genetic variation plays a role in disease risk and phenotype could identify potential therapeutic targets and inform clinical decision-making. Future In addition, clinical studies should be designed controlling for the genetic backgrounds of subjects, since disease phenotype and clinical outcomes and therapeutic responses may differ by genotype. Further understanding of these differences will allow the development of a personalized approaches to the IPF management.